Cross-Functional Influence in New Product Development: An Exploratory Study of Marketing and R…D Perspectives - Atuahene-Gima, Kwaku; Evangelista, Felicitas (Management Science, 2000)
Previous research in new product development (NPD) has focused on the participation of marketing and R…D personnel, but little attention has been paid to their influence. This study examined the effects of marketing's and R…D's influence and participation on new product performance and the differential effects of personal, new product, and organizational factors on their influence in the NPD process as seen from each other's perspective. The results suggest that marketing's and R…D's self-reported influence and their influence as reported by the other have a differential impact on new product performance. Unlike R…D's participation as perceived by marketing, marketing's participation as perceived by R…D affects new product performance only when its influence is high. The results also suggest that marketing's and R…D's influence in the NPD process is differentially affected by personal, new product, and organizational factors.